2022
DOI: 10.1002/ana.26409
|View full text |Cite
|
Sign up to set email alerts
|

Partial Restoration of Brain Dystrophin and Behavioral Deficits by Exon Skipping in the Muscular Dystrophy X‐Linked (mdx) Mouse

Abstract: Objectives Duchenne muscular dystrophy is associated with various degrees of cognitive impairment and behavioral disturbances. Emotional and memory deficits also constitute reliable outcome measures to assess efficacy of treatments in the mdx mouse lacking the muscle and neuronal full‐length dystrophins. The present study aimed to evaluate whether these deficits could be alleviated by the restoration of brain dystrophin. Methods We performed intracerebroventricular administration of a new potent tricyclo‐DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…Considering that ASO biodistribution in the CNS may be affected by various factors, such as ASO chemistry and charge, we used two different chemistries of ASO in this study: the Phosphorodiamidate Morpholino Oligomer (PMO) chemistry and the tricyclo-DNA (tcDNA) chemistry. PMOs have a neutral charge and are already approved by the FDA for the systemic treatment of DMD [ 8 ], while tcDNA is a charged, lipid-conjugated ASO that has previously shown therapeutic potential in mouse models of DMD [ 24 , 25 ]. Overall, our detailed comparative study provides useful insights into the local delivery and associated efficacy of ASOs in the CNS of mouse models of DMD.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that ASO biodistribution in the CNS may be affected by various factors, such as ASO chemistry and charge, we used two different chemistries of ASO in this study: the Phosphorodiamidate Morpholino Oligomer (PMO) chemistry and the tricyclo-DNA (tcDNA) chemistry. PMOs have a neutral charge and are already approved by the FDA for the systemic treatment of DMD [ 8 ], while tcDNA is a charged, lipid-conjugated ASO that has previously shown therapeutic potential in mouse models of DMD [ 24 , 25 ]. Overall, our detailed comparative study provides useful insights into the local delivery and associated efficacy of ASOs in the CNS of mouse models of DMD.…”
Section: Introductionmentioning
confidence: 99%
“…Dp427 loss particularly affects the number, size, and distribution of GABA A R clusters containing the α1 and/or α2 subunits within certain brain structures [ 5 , 39 ]. Preclinical studies have shown that Dp427 rescue by exon-skipping strategies in the adult brain of mdx mice has the potential to restore GABA A R clustering, as well as the associated excitatory-synapse plasticity and emotional disturbances [ 19 , 20 , 22 , 30 , 31 ]. This suggests that alterations of local inhibitory networks at least partly underlie the behavioral and cognitive deficits associated with DMD, and that changes in specific GABA A R subunits may serve as key readouts to evaluate the efficacy of genetic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting electropherograms were inspected to check whether automatic peak detection required any manual correction. A 6-point calibration curve was loaded, made of a mix of WT and dystrophin-deficient control lysates to obtain defined percentages of dystrophin (0, 5, 10, 15% or 0, 10, 15, 30% of corresponding WT tissues) as previously described for our Western blot analyses [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that in particular the number and position of guanine nucleotides in the 3′-end of the ASO increased toxicity, while there was a decrease when adenine nucleotides were substituted [ 27 ]. Recent studies demonstrated that reducing the PS content of ONDs leads to increased tolerability in the CNS [ 138 , 139 ].…”
Section: Toxicities Associated With Cns Local Deliverymentioning
confidence: 99%